Perlindungan Hukum Pemegang Hak Cipta Lagu dan Musik Di Era Digital - Surung B Simanjuntak; Bernard Nainggolan; Hendri Jayadi (Jurnal Syntax Transformation, 2022)
This research is motivated by the rampant exploitation of the use of youtube and facebook applications so that the rampant exploitation of music works that occur without knowledge by the creator or copyright holder. This is the negative influence of this technology so that it can remove the economic rights of creators and copyright holders. The form of research carried out in this paper is a form of diagnostic research, meaning that diagnostic research methods are research methods designed by guiding a researcher towards an action, so that with this research method researchers will be directed at the causes of the onset of a symptom. In particular, the protection needed by art people and in the world of the music industry is protection of economic rights and protection of moral rights. There is an economic gap seen in the world of the music industry against songwriters as song copyright holders compared to the fame of songs created, which means that the songs they create are in high demand by the public and played or listened to in various places over and over again. If a copyrighted work is said to be a related to the economy, most of the use of the song or music is always accompanied by economic activity (Nainggolan, 2016). The songwriters should be able to enjoy their intellectual property which the object of intellectual property (song / music) is so favored by other people. Intellectual Property Rights are the right to enjoy economically the results of an intellectual creativity, where the objects stipulated in the IPR are works that arise or are born due to human intellectual ability